The school factory of the history Historiography and conception of French Revolution in the school text of social sciences and history of the secondary education in Colombia - Mendoza, Miguel Ángel Gómez (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
The results are presented in a systematic analysis (qualitative and quantitative) content ‘latent’ or ‘deep’ that underwent the discursive corpus of the French Revolution found in fifty (50) school textbooks of Colombian history and social sciences between 1960-1999. It is considered what it is said about (discourse) on the French Revolution evolves throughout four studied decades, and it is narrowly related to the conception, the type or kind of revolution that is showed in the school texts. There are explained and understood with a wide validity the results of the documentary school study of the textbooks, when these are interpreted appealing to the diverse and opposite approaches and currents historiographies existing in the French and English historiography about this historic event, to “regulate” this modern revolution as: Atlantic revolution, western revolution, social revolution, political revolution, popular revolution and bourgeois revolution.